Green Production of Potassium Sulfate by Hydrothermal Carbonization of Carrageenan - Paolo O. Bantang, Jose; H. Camacho, Drexel (Asian Journal of Chemistry, 2020)
A novel green method of producing potassium sulfate from a sustainable source is described. Aqueous carrageenan is subjected to hydrothermal carbonization inside a pressure vessel. Separation of the liquid component from the hydrochar followed by evaporation to dryness and treatment with ethanol afforded potassium sulfate. Characterization using SEM-EDX, XRD and Raman spectroscopy confirms the identity of potassium sulfate in the form of K3H(SO4)2. The green process allows the facile release of sulfate ester group from the carrageenan chains and combining with the residual potassium ions in the carrageenan. The new method allows for the simplification of the process of producing potassium sulfate in an environmental friendly way and using a renewable source.